Effect of Fecal Microbiota Transplantation on Non-Alcoholic Fatty Liver Disease: A Randomized Clinical Trial - Xue, Lanfeng; Deng, Zhiliang; Luo, Wenhui; He, Xingxiang; Chen, Yu (Frontiers in Cellular and Infection Microbiology, 2022)
Background and Aims The clinical efficacy of fecal microbiota transplantation (FMT) in patients with non-alcoholic fatty liver disease (NAFLD) and the variant effects of FMT on lean and obese NAFLD patients remain elusive. Our study aimed to determine the clinical efficacy and safety of FMT for patients with NAFLD, elucidating its different influences on lean and obese patients with NAFLD. Methods We performed a randomized and controlled clinical trial. Patients in the non-FMT group were administered oral probiotics. In the FMT group, patients were randomized to receive FMT with donor stool (heterologous) via colonoscopy, followed by three enemas over 3 days. Both groups were also required to maintain a healthy diet and keep regular exercise for more than 40 min every day. They returned to the hospital for reexamination 1 month after treatment. Results FMT can decrease the fat accumulation in the liver by improving the gut microbiota dysbiosis, thus attenuating fatty liver disease. Significant differences in the clinical features and gut microbiota between lean and obese NAFLD patients were unveiled. Moreover, FMT had better effects on gut microbiota reconstruction in lean NAFLD than in obese NAFLD patients. Conclusions FMT could successfully improve the therapeutic effects on patients with NAFLD, and its clinical efficacy was higher in lean NAFLD than in obese NAFLD patients.